The Role of Effectiveness and Efficiency in the European Union's Counterterrorism Policy: The Case of Terrorist Financing - Michael Brzoska (Deutsches Institut für Wirtschaftsforschung (DIW), 2011)
European Union policy to counter terrorist financing is marked by uncertainty about causes and consequences. The paper addresses the role of evaluations of the effectiveness and efficiency of counter terrorist financing policies performed by international standard setting organizations in such a policy environment. It is found that assessments of effectiveness have shaped counter terrorist financing, but partially in a way biased towards their extension without strong evidence of their effectiveness. Assessments of the comprehensiveness of a regulatory framework and its implementation have been frequent while evaluations of the impact of activities on terrorist activities are largely lacking. As a result, there is much pressure to expand activities in the field without much knowledge about their impact. Considerations of financial and non-financial costs of counter terrorist financing measures have limited their extension, albeit again rarely based on evidence of their effectiveness. The paper's results confirm the proposition that policies in high risk fields tend to be expansive. Assessment of effectiveness and efficiency emphasizing output and outcome of measures rather than impact play an important role in shaping such expansion.
info:eu-repo/grantAgreement/EC/FP7/218105
Keywords: 330